Simultaneous Quantitative Determination of Polyphenolic Compounds in Blumea balsamifera (Ai-Na-Xiang, Sembung) by High-Performance Liquid Chromatography with Photodiode Array Detector. (18th March 2020) - Tan, Daopeng; Yang, Zhou; Zhang, Qianru; Ling, Hua; Du, Yimei; Lu, Yanliu; Xie, Tianpei; Zhou, Xumei; Qin, Lin; He, Yuqi
Abstract : A high-performance liquid chromatography method was developed for simultaneous quantification of 18 polyphenolic compounds from the leaves of Blumea balsamifera, including 17 flavonoids and 1 phenylethanone. The B. balsamifera extraction was separated by a Kromasil C18 column (250 × 4.6 mm, 5  μ m) with a binary gradient mobile phase consisting of acetonitrile and 0.2% aqueous acetic acid. A photodiode array detector (PDA) was used to record the signals of investigated constituents. The linearity, sensitivity, stability, precision, and accuracy of the established assay methods were assessed to meet the requirements of quantitative determination. Samples extracted by reflux in 25 mL of 80% methanol for 30 minutes were selected for the extraction method. The 18 compounds were accurately identified by comparing with the reference compounds. The purity of each peak was confirmed by the base peak in the mass spectrum. The contents of 18 compounds in Blumea samples from four different regions were successfully determined. The results also showed that 3, 3′, 5, 7-tetrahydroxy-4′-methoxyflavanone was the most abundant constituent, which could be used as a potential chemical marker for quality control of B. balsamifera and Chinese patent medications containing B. balsamifera herb.